The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.celrep.2017.02.048
|View full text |Cite
|
Sign up to set email alerts
|

Coupling between Protein Stability and Catalytic Activity Determines Pathogenicity of G6PD Variants

Abstract: Summary G6PD deficiency, an enzymopathy affecting 7% of the world population, is caused by over 160 identified amino acid variants in glucose-6-phosphate dehydrogenase (G6PD). The clinical presentation of G6PD deficiency is diverse, likely due to the broad distribution of variants across the protein and the potential for multidimensional biochemical effects. In this study, we use bioinformatic and biochemical analyses to interpret the relationship between G6PD variants and their clinical phenotype. Using struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 41 publications
1
44
0
Order By: Relevance
“…, α L ) is the amino-acid sequence considered, L is its length, and ∆ l (α l ) is the mutational effect on the trait T of a mutation to amino acid α l at site l. Mutational effects can be measured with respect to a reference sequence α 0 , satisfying ∆ l (α 0 l ) = 0 for all l. Eq. 1 is very general as it amounts to saying that, to lowest order, mutations have an additive effect on the trait T , which can be any relevant physical property of the protein, say its binding affinity, catalytic activity, or thermal stability [12]. System-specific details are encoded by the single-site mutational effects ∆ l (α l ), which can be measured experimentally.…”
Section: Selection On An Additive Traitmentioning
confidence: 99%
“…, α L ) is the amino-acid sequence considered, L is its length, and ∆ l (α l ) is the mutational effect on the trait T of a mutation to amino acid α l at site l. Mutational effects can be measured with respect to a reference sequence α 0 , satisfying ∆ l (α 0 l ) = 0 for all l. Eq. 1 is very general as it amounts to saying that, to lowest order, mutations have an additive effect on the trait T , which can be any relevant physical property of the protein, say its binding affinity, catalytic activity, or thermal stability [12]. System-specific details are encoded by the single-site mutational effects ∆ l (α l ), which can be measured experimentally.…”
Section: Selection On An Additive Traitmentioning
confidence: 99%
“…However, the main question is whether the poor enzyme activity of the G6PD mutants in a relatively long-lived non-nucleate cell is due to instability of the active form or if they are kinetically defective [16]. In this regard, Cunningham et al [32] demonstrated that the clinical phenotypes of G6PD variants were largely determined by a trade-off between protein stability and catalytic activity by using a multidimensional analysis of biochemical data.…”
Section: Analysis Of the Stability Of The G6pd Enzymesmentioning
confidence: 99%
“…[9] Products of the PPP are important for the biosynthesis of nucleotides and fatty acids. [11] For example, mutations affecting the homodimer interface of G6PD are particularly pathogenic, as only the homodimerica nd homotetrameric oligomers of G6PD are stable and activei nvivo. Despite the critical role G6PD plays in the cell, G6PD deficiencyi st he second most commonh uman enzymopathy;m ore than 160 single-nucleotide substitutions that alter enzymatic activity and/ors tability have been identified in humans.…”
mentioning
confidence: 99%
“…[10] Missense mutations result in av ariety of clinicalp henotypesd epending on the naturea nd location of the mutation. [11] For example, mutations affecting the homodimer interface of G6PD are particularly pathogenic, as only the homodimerica nd homotetrameric oligomers of G6PD are stable and activei nvivo. [12] G6PD is the only enzyme known to have evolved as econd NADP + binding site, closetothe dimer interface;this second so-called structural site is essential for maintaining the activity,s tability,a nd oligomeric state of the enzyme.…”
mentioning
confidence: 99%